2004
DOI: 10.1007/s10086-003-0535-9
|View full text |Cite
|
Sign up to set email alerts
|

Condensation reactions of phenolic resins IV: self-condensation of 2,4-dihydroxymethylphenol and 2,4,6-trihydroxymethylphenol (2)

Abstract: Kinetics of the self-condensation of 2,4dihydroxymethylphenol (2,4-DHMP) and 2,4,6trihydroxymethylphenol (THMP) were investigated to elucidate the mechanisms of the condensation of hydroxymethylphenols (HMPs). Rate equations were derived on the assumptions of the formation of quinone methide intermediates as unimolecular reactions and the occurrence of bimolecular reactions between undissociated HMPs, between undissociated HMP and dissociated HMP, and between dissociated HMPs. Rate constants were determined nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The kinetics and mechanisms of the individual reactions in the PF system are apparently the key issues and also the foundation for understanding the chemistry of PF. However, by surveying the literature from the middle of the last century to recent years, discrepant results for the kinetics and mechanisms of the base-catalyzed condensation reactions between hydroxymethylphenols (HMPs) have been reported [9,10,11,12,13,14,15,16,17,18,19]. In some earlier studies, the condensations of HMPs were reported to be first-order [9,10,11], pseudo-first-order or second-order [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics and mechanisms of the individual reactions in the PF system are apparently the key issues and also the foundation for understanding the chemistry of PF. However, by surveying the literature from the middle of the last century to recent years, discrepant results for the kinetics and mechanisms of the base-catalyzed condensation reactions between hydroxymethylphenols (HMPs) have been reported [9,10,11,12,13,14,15,16,17,18,19]. In some earlier studies, the condensations of HMPs were reported to be first-order [9,10,11], pseudo-first-order or second-order [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Higuchi et al confirmed that the self-condensation of 2-hydroxymethylphenol (2-HMP) is kinetically of genuine first-order and the QM hypothesis seems to hold in such a reaction [ 15 ]. However, in their continuous studies on 4-hydroxymethylphenol (4-HMP) [ 16 ], 2,4-dihydroxymethylphenol (2,4-DHMP) [ 17 ] and 2,4,6-trihydroxymethylphenol (2,4,6-THMP) [ 18 ], the condensations appeared to be of fractional order, ranging from 1.1~2.0. Further, the reaction order varied with the change of the NaOH/HMP molar ratio and with the change of the HMP concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these results together with previous kinetic works, 9,10 we assume a reaction pathway for the self-condensation of THMP (Fig. 5).…”
Section: Discussionmentioning
confidence: 90%
“…The behavior of monomeric HMPs as model compounds is easier to study. In previous works, the kinetics of the self-condensations of 2-hydroxymethylphenol, 7 4-hydroxymethylphenol, 8 2,4-dihydroxymethylphenol, and 2,4,6-trihydroxymethylphenol (THMP) 9,10 were investigated. At THMP concentrations greater than 1.5 mol/ L, the reaction order was 2.0, whereas at concentrations below 1.0 mol/L, the reaction order changed to values between 1.2 and 1.6.…”
Section: Introductionmentioning
confidence: 99%
“…Pathway (II) demonstrates the mechanism that forms the intermediates D , E and F for the base-catalyzed phenol-formaldehyde reaction. Among them, the quinine methide is the widely accepted intermediate that is involved in the condensations [40,41,42]. Based on these intermediates, the mechanisms for the UF and PF condensation reactions were proposed in Figure 3.…”
Section: Resultsmentioning
confidence: 99%